TU8.11 Improving the efficiency of the EGS service in a University Teaching Hospital. Smarter application of standards and use of resources. (9th August 2022) - Bose, Sayantan; Baltatzis, Minas; Carlson, Gordon
Abstract: Aim: Effective utilization of resources for emergency general surgery (EGS) is essential for operational efficiency. Many patients have pathology with a time-dependent outcome and clinical standards have been established regarding timing of surgical intervention. The aim of this study was to investigate barriers to the delivery of timely EGS. Methods: The delivery of EGS between 31/01/21 and 30/08/21 was studied. All cases were reviewed to determine clinical urgency, appropriateness of "urgency" within the clinical context (diagnosis, NEWS-2 score) and timing of EGS. Discrepancies between theatre booking and clinical need and delay in undertaking EGS compared with the relevant clinical standards were identified. Results: EGS was undertaken in 520 patients (262M:258 F), mean age 49 (16–101) years. 34(6%) were booked as needing "immediate", 130 (25%) "urgent 2–6hr", 242 (47%) "urgent 6–18 hr" and 114 (22%) "expedited" EGS. In 373 (71.7%), EGS was undertaken in a time frame which met (or exceeded) relevant standards. In 235 (45%) cases, the urgency of booking exaggerated clinical need. EGS was "delayed" in 147 (28.3%) cases when compared with urgency as booked, but when actual clinical need was reviewed EGS was delayed in only 66 cases (12.7%). Delay was due to unavailability of facilities in 25 (38%) of cases, whereas in 24 (36%) treatment was delayed purely "overnight". Conclusion: Inappropriate allocation of clinical urgency resulted in the majority of "delayed" EGS. The routine application of RCS18 standards would prevent this. Avoiding delay overnight and an increase in theatre resource would improve efficiency.